Co-sensitization promoted light harvesting with a new mixed-addenda polyoxometalate [Cu(C12H8N2)2]2[V2W4O19]·4H2O in dye-sensitized solar cells. Issue 42 (7th October 2015) - Xu, Sha-Sha; Chen, Wei-Lin; Wang, Yan-Hua; Li, Yang-Guang; Liu, Zhu-Jun; Shan, Chun-Hui; Su, Zhong-Min; Wang, En-Bo
Abstract : [Cu(C12 H8 N2 )2 ]2 [V2 W4 O19 ]·4H2 O-doped TiO2 composites were introduced into the dye-sensitized solar cells as co-sensitizers in N719-sensitized photoanodes to enhance the photoelectric conversion efficiency. Abstract : A di-vanadium-substituted Lindqvist-type polyoxometalate [Cu(C12 H8 N2 )2 ]2 [V2 W4 O19 ]·4H2 O (1 ) was hydrothermally synthesized and characterized structurally by single crystal X-ray diffraction analysis. X-ray photoelectron spectroscopy and energy disperse spectroscopy tests further prove the existence of vanadium. Ultraviolet photoelectron spectroscopy and density functional theoretical studies indicate that the energy level of1 matches well with the conduction band of the TiO2 . Furthermore, considering the semiconductor-like nature of1 and the introduction of transition metal element Cu synchronously extends the absorption to the visible region, which should also be beneficial to the photovoltaic device performance.1 -Doped TiO2 composites (denoted as1 @TiO2 ) have been successfully fabricated by a simple sol–gel method, and introduced into the dye-sensitized solar cells (DSSCs) as co-sensitizers in N719-sensitized photoanodes by mixing1 @TiO2 with P25 nanoparticles with different weight ratios to enhance the photoelectric conversion efficiency. The investigations show that the DSSC assembled with1 @TiO2 /19P25 photoanode has the best performance and the overall improvement of the efficiency is 21.6% compared with pure P25. Furthermore, the electrochemical impedance spectroscopy and open-circuit voltage decay investigations show that the cosensitization of1 and N719 can promote electron transfer and restrain charge recombinations in the DSSCs, resulting in a longer electron lifetime.